The Puerto Rican parrot reintroduction program: Sustainable management of the aviary population. Issue 2 (7th January 2014) - Earnhardt, Joanne; Vélez‐Valentín, Jafet; Valentin, Ricardo; Long, Sarah; Lynch, Colleen; Schowe, Kate
<x xml:space="preserve">Abstract</x> The cornerstone of the recovery plan for the critically endangered Puerto Rican parrot (Amazona vitatta) is an actively managed, long‐term reintroduction program. One captive population distributed across two aviaries in Puerto Rico is the sole source for release but its ability to persist as a managed resource has not been evaluated since 1989. We conducted an assessment for sustainable management of the aviary population while harvesting for release. To assess demographic rates such as population growth, vital rates, and age/sex structure, we compiled a studbook database on all living, dead, and released individuals in the aviary population. Using an individual‐based risk assessment model we applied population specific data based on the management period from 1993 to 2012 to simulate future aviary population dynamics and evaluate future potential production. We modeled four potential management strategies to harvest parrots for proposed releases; these scenarios vary the number of parrots and the life stage. Our simulations revealed that the aviary population can be simultaneously managed for sustainability and harvesting of parrots for release. However, without cautious management, overharvesting can jeopardize sustainability of the aviary population. Our analysis of the aviary breeding program provides a rare opportunity to review progress relative to conservation program objectives after four decades of active management. The successful growth of the aviary population and its ability to serve as a sustainable source for reintroductions supports the 1973 decision to build a breeding program from a small population of 13 parrots. Zoo Biol. 33:89–98, 2014. © 2014 Wiley Periodicals Inc.